The combined presence of H pylori infection and gastro-oesophageal reflux disease leads to an up-regulation of CDX2 gene expression in antrum and cardia. Issue 3 (27th February 2009) - Bornschein, J; Wex, T; Peitz, U; Kuester, D; Roessner, A; Malfertheiner, P
Abstract : Background: CDX2 is an epithelial transcription factor that regulates intestinal differentiation and is involved in the development of intestinal metaplasia (IM). Aim: To analyse the expression of CDX2 in the gastric mucosa in various locations and its relationship to Helicobacter pylori infection and gastro-oesophageal reflux disease (GORD). Methods: 69 patients with upper gastrointestinal symptoms were stratified into four groups according to their H pylori and GORD status. Patients without infection and without GORD were the reference group ( H pylori (−)/GORD(−)). Biopsies from the antrum, corpus and cardia were assessed by histopathology according to the updated Sydney System. CDX2 transcription levels were determined by quantitative RT-PCR and immunohistochemistry. Results: CDX2 gene expression was significantly up-regulated in antral and cardia mucosa of patients with both H pylori infection and GORD (26- and 100-fold, respectively; p<0.05), but remained unchanged in corpus mucosa. If only H pylori infection or GORD was present, CDX2 expression levels were 6- to 11-fold increased in the antrum, but without reaching statistical significance. CDX2 expression correlated positively with the degree of IM (p<0.01) and the degree of H pylori induced inflammation (p<0.05). Gene expression data were confirmed immunohistochemically by the detection of CDX2 in areas of IM and in focally distributed CDX2-expressing cells in non-metaplastic gastric mucosa. Conclusions: The combined presence of H pylori infection and GORD leads to an up-regulation of CDX2 gene expression in cardia and antral mucosa, but not in the corpus.